(untitled) (Malaysian Management Journal, 2010)
This study investigates the relationship between Islamic cultural values and corporate social accountability among Muslim accountants in Malaysia. Two independent variables are proposed namely collectivism and power distance. Multivariate analysis was employed to examine the relationship between the variables in the framework and 124 respondents participated in this study. It is found that there is no relationship between collectivism and corporate social accountability. On the other hand, there is a significant positive relationship between power distance and corporate social accountability. In conclusion this study recommends that the understanding on zakat and equality should be given utmost priority in order to increase the level of social accountability among Muslim accountants in Malaysia. Such learning activities should be given continuous professional development (CPD) point by the Malaysian Institute of Accountants (MIA) as a motivation.